Modeling of evanescent-wave coupling between optical dielectric waveguides. (2nd January 2019) - Abouheaf, M.; Gueaieb, W.; Samra, A.
Abstract: The transverse coupling between the optical dielectric waveguides is modeled and analyzed using the Improved Coupled Mode Theory. The coupling between the modes is established via the evanescent part of the modal field propagating in one waveguide which penetrates the adjacent waveguide. The coupling phenomena is analyzed numerically by evaluating the average overlap integrals, coupling coefficients, asynchronism factor, and coupling length using the Improved Coupled Mode Theory at strong and weakly guiding conditions. The performance of the Improved Coupled Mode Theory is tested and compared to the conventional Coupled Mode Theory.